Plant biomass as potential economic commodities for agricultural purposes - Obuseng, Veronica C.; Moshoeshoe, Mohau N.; Nareetsile, Florence M.; Kwaambwa, Habauka; Maina, Irene (Frontiers in Chemistry, 2022)
The world’s population is growing continually and is projected to reach nine billion by the year 2050. This growth rate requires increased and economically viable food production and adequate supply of quality water to sustain life. Increased food production and supply of water requires adding fertilizers and possible recycling of wastewater, to address improvement of soils’ nutritional status and potable water shortages. The objectives of this work were to determine the nutrients in sewage impacted wastewater, borehole water, agricultural waste, and commercial fertilizer (control) material and their heavy metal content was also carried out to determine their suitability for use. In addition, Moringa seed pods and Morula nutshells were investigated as a bio remedial approach for removal of toxic metals from aqueous samples. An attempt to regenerate sorbent was made since the saturated sorbents that contain the metal ions are not safe for disposal as they can pollute the environment. Nutrients were analysed by HPLC, while metals were analysed using Varian 220FS Atomic Absorption spectrometer operated with air/acetylene. Nonedible agricultural materials were found to contain appreciable amounts of plant nutrients such as nitrates (NO3-), nitrites (NO2-) and phosphates (PO43-) as well as metal ions such as magnesium, copper and zinc which are beneficial for plant growth. Results obtained on analysis of sewage water effluent showed that heavy metal and nutrient concentrations decreased with treatment stage. The utilization of Moringa Oleifera seedpods for metal removal from wastewater is viable and would reduce costs for waste disposal and can offer alternatives to conventional methods for removal of unwanted or toxic species from the environment. It showed potential in removing selected metal ions such as Pb, Cd, Cu, Fe and Zn from polluted water. This organically treated wastewater is environmentally friendly and may be used for applications which do not require potable water such as irrigating golf courses, lawns and crops or industrial purposes, if proper measures are taken to ensure its quality.